EFFECTIVENESS OF PUBLIC-PRIVATE PARTNERSHIPS FOR MODERNIZING THE SYSTEM OF VOCATIONAL EDUCATION AND TRAINING FOR SKILLS DEVELOPMENT: FOREIGN EXPERIENCE (Innovative professional education, 2023)
Vocational education and training (VET) is important because it contributes to the creation of jobs for sustainable living and provides the training needed to keep up with the dynamic and ever-changing standard of living in a rapidly growing technological world. VET is the training that any country needs to promote its socio-economic development. The UNESCO and ILO recommendations have contributed to the introduction of major reforms around the world aimed at updating or modernizing VET for sustainable professional development. What national governments need most is to successfully implement their policy initiatives to make VET effective in developing skills to reduce unemployment. This requires reforming VET through public-private partnerships, making huge investments, demonstrating ongoing commitment, and ensuring that VET is portrayed in the right way in the eyes of the public. The thesis examines public-private partnerships in VET from the perspective of conceptual issues. The need for public-private partnerships in VET, reforms in VET, models of PPP for skills development, benefits of PPPs for VET, ways to modernize VET through PPPs for skills development.
Keywords: public-private partnerships (PPPs), vocational education and training (VET), professional skills, private sector